Setting up proinnovative networks in Silesia - Jan Stachowicz; Stanisław Walukiewicz (European Regional Science Association (ERSA), 2003)
Silesia is the most industrialized region of Poland recently under huge reindustrialization in an effort to change its heavy industrial pattern into more diversified and innovative one. The reindustrialization processes is additionally complicated by the transformation of Polish economy from central planned to marked oriented. Proinnovative networks, in which under more or less formally conditions cooperate industrial/service companies, research/educational institutions, regional/central governments, professional bodies and even private persons, are put forward as a possible way to solve the reindustrialization problems. Their importance is emphasized in the Regional Development Strategy for Silesia, 2000-2015. The aim of present paper is to study factors and phenomena, which facilitate cooperation of partners within proinnovative networks, as well as describe problems, which are, faced both when setting up such a network and in its day by day business. Special attention is paid to so-called soft factors, the social capital of partners cooperating in the network. We introduce certain measures of social capital and demonstrate their usefulness. In second part of the paper we present a number of case studies of Silesia proinnovative networks. For each network we describe its objective, short history with results achieved so far, and future plans. We pay special attention to these networks, which are considered, at least in part, as the results of projects under the Framework Programmes of European Union.
Keywords: 330